Modelling the focal stage of the strain field distribution in highly stressed rock - Ksendzenko Ludmila S. (Федеральное государственное автономное образовательное учреждение высшего образования «Дальневосточный федеральный университет», 2015)
The article deals with the non-Euclidian continuum model applied to describe the stress-strain state of highly stressed rock at the pre-failure stage. The oscillating character of the distribution of stresses both along the perimetre of the rock and along its height has been demonstrated in it. A satisfactory convergence of the results of the theoretical researches with the experimental data has been obtained.
Keywords: ОБРАЗЕЦ ГОРНОЙ ПОРОДЫ; SAMPLE OF ROCK; ОДНООСНОЕ СЖАТИЕ; UNIAXIAL COMPRESSION SIMULATION; НЕКЛАССИЧЕСКОЕ ПОЛЕ НАПРЯЖЕНИЙ; NON-CLASSICAL FIELD OF STRESS; 622.831